2017
DOI: 10.1002/cne.24309
|View full text |Cite
|
Sign up to set email alerts
|

Pedal peptide/orcokinin‐type neuropeptide signaling in a deuterostome: The anatomy and pharmacology of starfish myorelaxant peptide in Asterias rubens

Abstract: Pedal peptide (PP) and orcokinin (OK) are related neuropeptides that were discovered in protostomian invertebrates (mollusks, arthropods). However, analysis of genome/transcriptome sequence data has revealed that PP/OK‐type neuropeptides also occur in a deuterostomian phylum—the echinoderms. Furthermore, a PP/OK‐type neuropeptide (starfish myorelaxant peptide, SMP) was recently identified as a muscle relaxant in the starfish Patiria pectinifera. Here mass spectrometry was used to identify five neuropeptides (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(93 citation statements)
references
References 65 publications
5
85
3
Order By: Relevance
“…Consistent with this pattern of expression, intense immunostaining was also observed in the lateral motor nerves, components of the starfish nervous system that were first described based on analysis of histochemical staining (Smith, ). Investigation of the in vitro pharmacological effects of ArPPLN1b revealed that it causes dose‐dependent relaxation of three preparations from A. rubens —apical muscle, tube feet and cardiac stomach (Lin, Egertová et al, ), consistent with previous findings from P. pectinifera (Kim et al, ). Thus, collectively the data obtained from experimental studies on SMP/PPLN1‐type neuropeptides in P. pectinifera and A. rubens indicate that a physiological role of these peptides is to act as inhibitory neuromuscular transmitters or modulators in starfish.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with this pattern of expression, intense immunostaining was also observed in the lateral motor nerves, components of the starfish nervous system that were first described based on analysis of histochemical staining (Smith, ). Investigation of the in vitro pharmacological effects of ArPPLN1b revealed that it causes dose‐dependent relaxation of three preparations from A. rubens —apical muscle, tube feet and cardiac stomach (Lin, Egertová et al, ), consistent with previous findings from P. pectinifera (Kim et al, ). Thus, collectively the data obtained from experimental studies on SMP/PPLN1‐type neuropeptides in P. pectinifera and A. rubens indicate that a physiological role of these peptides is to act as inhibitory neuromuscular transmitters or modulators in starfish.…”
Section: Introductionsupporting
confidence: 81%
“…The structures of neuropeptides derived from ArPPLNP2 were determined by MS/MS analysis of A. rubens radial nerve cords extracted in 90% methanol/9% acetic acid, employing use of methods described previously (Lin, Egertová et al, ; Lin, Mita et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations